The Gold Nanoparticles Array on CdS Semiconductor Films: Fabrication, Morphology and Optical Properties - V. Kusnezh; R. Petrus’; H. Il’chuk; O. Tuziak; I. Zachek; V. Rodych (Журнал нано- та електронної фізики)
The possibility of fabrication of gold nanoparticles arrays on CdS semiconductor films by thermal annealing (673 K, 60 min) in vacuum (P ~ 1,3 Pa) of gold films with the thickness of 6 nm was considered. The surface morphology of CdS films covered by gold nanoparticles array was investigated and the average sizes of nanoparticles were determined. The absorption and transmission spectra of the samples in the visible region were measured, and the wavelengths of plasmon resonance were defined. The influence of gold nanoparticles array on the energy gap of CdS films was found.